2005
DOI: 10.1016/j.econlet.2005.05.024
|View full text |Cite
|
Sign up to set email alerts
|

Re-examining inflation and inflation uncertainty in developed and emerging countries

Abstract: This study examines the relationship between inflation and inflation uncertainty for both developed and emerging countries using the asymmetric power GARCH model. We find new evidence that suggests that positive inflationary shocks have stronger impacts on inflation uncertainty for mainly Latin American countries. We also find that inflation causes inflation uncertainty for most countries but the evidence for causality of the opposite direction is mixed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
73
1
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(85 citation statements)
references
References 18 publications
(17 reference statements)
7
73
1
3
Order By: Relevance
“…Our results for inflation rate dependence differ to some extent from those of Daal et al (2005) who found evidence to support the Friedman-Ball hypothesis for all countries except Germany. The contrasting results are most likely due to the difference in the econometric specification and tests employed in this study.…”
Section: A Test For Level Dependence and Asymmetric Inflation Uncertacontrasting
confidence: 57%
See 2 more Smart Citations
“…Our results for inflation rate dependence differ to some extent from those of Daal et al (2005) who found evidence to support the Friedman-Ball hypothesis for all countries except Germany. The contrasting results are most likely due to the difference in the econometric specification and tests employed in this study.…”
Section: A Test For Level Dependence and Asymmetric Inflation Uncertacontrasting
confidence: 57%
“…2 Nas andPerry (1998), Fountas (2001), Hwang (2001), Apergis (2004) and Kontonicas (2004) employ GARCH models in studying the relationship between inflation and its uncertainty. 3 See, amongst others, Grier and Perry (1998) and Daal et al (2005). absolute magnitude.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These authors did not find empirical support for the Friedman hypothesis. However, it has been supported by Joyce (1995), Baillie et al (1996), Grier and Perry (1998), Kim and Nelson (1999), Kontonicas (2004), Conrad and Karanasos (2005) and Daal et al (2005) among many others. Finally, there are studies as, for example, Hwang (2001), that find a negative relationship between level of inflation and its future uncertainty.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Brunner and Hess (1993) (who suggested to take into account the asymmetry in the influence of shocks on the volatility), Baillie, Chung, and Tieslau (1996) (who used the ARFIMA-GARCH model featuring long memory), Kontonikas (2004), Fountas, Karanasos, and Kim (2006), Henry, Olekalns, and Suardi (2007). Probably the most representative study of this kind in terms of the number of countries is Daal, Naka, and Sanchez (2005). The study used CPI from 23 countries to estimate a model of inflation including the asymmetric power GARCH model for conditional variance.…”
Section: Inflation-uncertainty Literature: Empirical Evidencementioning
confidence: 99%